2017
DOI: 10.1016/j.bbadis.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

The galactose-induced decrease in phosphate levels leads to toxicity in yeast models of galactosemia

Abstract: Classic galactosemia is an inborn error of metabolism caused by deleterious mutations in the GALT gene. A number of evidences indicate that the galactose-1-phosphate accumulation observed in patient cells is a cause of toxicity in this disease. Nevertheless, the consequent molecular events caused by the galactose-1-phosphate accumulation remain elusive. Here we show that intracellular inorganic phosphate levels decreased when yeast models of classic galactosemia were exposed to galactose. The decrease in phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…We considered whether accumulation of toxic metabolites might account for cell wall biosynthesis defects. However, toxic metabolites that accumulate, e.g., in S. cerevisiae models of galactosemia (64,65) and fructose intolerance (65), are sugar phosphates, i.e., their biosynthesis requires a phosphorylation step whose substrate was scarce in cells lacking Pho84. Accordingly, we did not identify potentially toxic metabolites among the significantly dysregulated metabolites in these cells (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…We considered whether accumulation of toxic metabolites might account for cell wall biosynthesis defects. However, toxic metabolites that accumulate, e.g., in S. cerevisiae models of galactosemia (64,65) and fructose intolerance (65), are sugar phosphates, i.e., their biosynthesis requires a phosphorylation step whose substrate was scarce in cells lacking Pho84. Accordingly, we did not identify potentially toxic metabolites among the significantly dysregulated metabolites in these cells (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Though the null mutant could grow in glucose, its growth rate was significantly reduced ( Figure 5). The gal1D/D mutant was able to grow in the medium with 1% glucose and 1% galactose with a much lower rate and a half efficiency as compared with the wild-type 11-3002, suggesting that galactose was probably unable to enter into the cells of the mutant without GAL1; otherwise, the unmetabolized galactose would be lethal to the yeast cells [34][35][36]. HPLC analysis showed that the concentration of galactose remained unchanged during the growth course of the 11-3002gal1D/D mutant in the medium with 1% glucose and 1% galactose, though the cells grew well, and glucose was exhausted ( Figure S4A), confirming that galactose was unable to be transferred into the cells of the mutant.…”
Section: The Function Of Gal2 Requires Other Structural Gal Genesmentioning
confidence: 99%
“…This cyclical phosphorylation and dephosphorylation of galactose could deplete cellular ATP levels, leading to cellular toxicity. 19,20 Machado et al 21 have suggested that cellular toxicity may be due to trapping of phosphate in Gal-1P, leading to intracellular inorganic phosphate depletion. Using a yeast model of Classic Galactosaemia, the authors showed that supplementation of phosphate suppressed the toxic effects of galactose in yeast cells.…”
Section: Cellular Toxicity Of Gal-1pmentioning
confidence: 99%